Teaching high school students to use online consumer health resources on mobile phones: outcome of a pilot project in Oyo State, Nigeria (2019)
This project evaluated the outcomes of training high school students to deliver consumer health information to their peers. A total of 120 students selected from 7 high schools in Oyo state, Nigeria, received 8 hours of training on consumer health literacy and peer education, which is a process of training volunteers to deliver health information to their peers. The training included hands-on activities using the students’ own mobile phones. After the training, peer educators distributed leaflets, showed consumer health information (CHI) websites to others, counseled and referred fellow students, and submitted forms describing these activities. All peer educators completed pre- and post-tests, and 10 were interviewed 4 months after training. After the training, the authors found improvement in the trainees’ knowledge of CHI resources and understanding of their roles as peer educators. Most peer educators (72.5%) delivered CHI to their peers after the training, primarily through sharing websites on teen health and other CHI resources. In the interviews, all peer educators reported direct benefits from participating in the project, and many stated that they knew where to find reliable health information. Volunteer high school students can be trained to deliver CHI to their peers using mobile phones.